Reite Plants An Ethnobotanical Study in Tok Pisin and English - Nombo, Porer (Asia-Pacific Environment Monographs, 2010)
Reite Plants is a documentation and discussion of the uses of plants by speakers of the Nekgini language, a people who reside in the hinterland of the Rai Coast in northern Papua New Guinea. High quality images and detailed information about traditional customary practices using plants provide a unique entry into understanding Nekgini social and cultural life. The book contains a discussion of the ownership of plant knowledge in the context of both local and contemporary global trends. As a dual language, co-authored text, the book is a unique contribution to the ethnobotany and anthropology of Melanesia. Reite Plants represents the product of a long term collaborative work between the authors. This book makes an important contribution ... Nombo and Leach provide an exciting example of how much a deeper exploration of cultural context adds to the field of ethnobotany. It will make very good company with the classic ethnobiological collaborative work of Saem Majnep and Ralph Bulmer on the birds and animals of the Madang highlands. Robin Hide, The Australian National University